A proportional assist ventilator to unload respiratory muscles experimentally during exercise in humans. Issue 6 (28th April 2016) - Dominelli, Paolo B.; Henderson, William R.; Sheel, A. William
New Findings: What is the central question of this study? Can a modern proportional assist ventilator (PAV) function sufficiently well to unload the respiratory muscles during exercise? What is the main finding and its importance? A PAV can be constructed with contemporary hardware and software and be used at all exercise intensities to unload the respiratory muscles by up to 70%. Previously, PAVs have allowed researchers to address many fundamental physiological problems in clinical and healthy populations, but those versions are no longer functional or available. We describe the creation of a PAV that permits researchers to use it as an experimental tool. Manipulation of the normally occurring work of breathing (WOB) during exercise can provide insights into whole‐body regulatory mechanisms in clinical patients and healthy subjects. One method to reduce the WOB uses a proportional assist ventilator (PAV). Suitable commercially available units are not capable of being used during heavy exercise. This investigation was undertaken in order to create a PAV and assess the degree to which the WOB could be reduced during exercise. A PAV works by creating a positive mouth pressure ( P m ) during inspiration, which consequently reduces the WOB. Spontaneous breathing patterns can be maintained, and the amplitude of P m is calculated using the equation of motion and predetermined proportionality constants. We generated positive P m using a breathing apparatus consisting of rigid tubing, solenoid valves to control the airflow direction and a proportional valve connected to compressed gas. Healthy male and female subjects were able to use the PAV successfully while performing cycling exercise over a range of intensities (50–100% of maximal workload) for different durations (from 30 s to 20 min) and different protocols (constant versus progressive workload). Inspiratory WOB was reduced up to 90%, while total WOB was reduced by 70%. The greatest reduction in WOB (50–75%) occurred during submaximal exercise, but at maximal ventilations (>180 l min −1 ) a 50% reduction was still possible. The calculated change in WOB and subsequent reduction in respiratory muscle oxygen consumption resulted in equivalent reductions in whole‐body oxygen consumption. With adequate familiarization and practice, our PAV can consistently reduce the WOB across a range of exercise intensities. Abstract :